Miradas y reflexiones sobre Gentile Bellini quinientos años después de su fallecimiento - Suárez Quevedo, Diego (Anales de Historia del Arte, 2007)
Searchs about Gentile Bellini, on the ocassion of the V centenary of his death, before and after his voyage to Istambul and its meaning, with the testimony of masterpieces, in the social and artistic context of Venice between 15th and 16th centuries.